(untitled) (The Shivapuri Journal, 2025)
The Allied campaigns preceding the landings in the beaches of Normandy shaped the perceptions and thinking of allied commanders on how to conduct a large-scale invasion against the German held defences in France in the later stages of World War II. One such campaign in Sicily in the summer of 1943, “Operation Husky”, is a study in case as to whether that campaign could be taken as a success or failure for the Allies in terms of meeting the desired end state. This paper examines the various events of the Sicily campaign and tries to identify how the concept of a desired end state can help to judge the success or failure of the campaign. Using information presented in academic and government literature as well as the documents from military history, the paper concludes that the lack of a clearly formulated desired end state allowed the political and military leadership to exercise enhanced flexibility which ultimately contributed towards achieving the strategic outcome of the campaign. The paper covers the definitions of end state at multiple levels and compares these with Husky. It also deals with how the relationship between operation and strategy played out during the Sicily campaign and concludes by emphasizing on the need to have synchronization between strategy and operation.